1988
DOI: 10.1042/bj2530481
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluoromethylornithine, an irreversible and specific inhibitor of l-ornithine:2-oxo-acid aminotransferase

Abstract: 5-Fluoromethylornithine (5-FMOrn) is the first specific irreversible inhibitor of L-ornithine:2-oxoacid aminotransferase (OAT) found. Single doses (greater than 10 mg/kg) of this compound inactivate OAT to a residual OAT-like activity. This activity (10-20% of total activity) is resistant to further inactivation by higher or repeated doses of 5-FMOrn, or incubation with the inactivator in vitro. Ornithine concentrations are greatly enhanced in various tissues, and urinary ornithine is dramatically increased, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
0
31
1
Order By: Relevance
“…OAT is inhibited by aminohexanoate [35], GABA, gabaculine, 5-fluoromethylornithine (5-FMOrn) [20,36,37,38], and l -canaline [39]. A more complete list of inhibitors and their structures is given in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…OAT is inhibited by aminohexanoate [35], GABA, gabaculine, 5-fluoromethylornithine (5-FMOrn) [20,36,37,38], and l -canaline [39]. A more complete list of inhibitors and their structures is given in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the findings that GABA-T and ORN-T are closely related in terms of structure and activity [28], and that all reported GABA-T inhibitors, except for ethanolamine-O-sulfate and vigabatrin, are also inhibitors of ORN-T [28][29][30]. Furthermore, selective inhibition of ORN-T, which is heavily concentrated in nerve terminals [31], leads to accumulation of synaptic ORN [32] and drastically elevates ORN levels in the rodent brain [33,34]. It should be noted that aside from this direct effect of PLZ, ORN-T may also be indirectly inhibited by PLZ, as GABA itself is a competitive inhibitor of ORN-T, acting as part of a negative-feedback mechanism to regulate ORN-T activity in vivo [35].…”
Section: Discussionmentioning
confidence: 95%
“…OAT activities in the RPE cells were assayed as described previously (Daune, Gerhart and Seiler, 1988). The standard assay mixture contained 175 m -ornithine, 35 m α-ketoglutarate, 80 µ pyridoxal phosphate, 50 m potassium phosphate buffer (pH 8n0) and 300 µl of cell extracts in a 1 ml volume.…”
Section: Oat Assaymentioning
confidence: 99%
“…It was demonstrated that 5-FMOrn inactivated OAT, but none of the other enzymes involved in ornithine metabolism, such as γ-aminobutyric acid-α-ketoglutaric acid transaminase, -ornithine decarboxylase or -ornithine carbamoyltransferase (Daune, Gerhart and Seiler, 1988). To confirm the inactivation of OAT in each phenotype of RPE cells, 0n5 m 5-FMOrn was added to the cells that had been plated onto 6 well plates at 5i10& cells well −" .…”
Section: Inactivation Of Oat By 5-fmornmentioning
confidence: 99%
See 1 more Smart Citation